Primary Surplus Behavior and Risks to Fiscal Sustainability in Emerging Market Countries : A "Fan-Chart" Approach - Celasun, Oya (IMF Working Papers; Working Paper, 2006)
This paper proposes a probabilistic approach to public debt sustainability analysis (DSA) using "fan charts." These depict the magnitude of risks-upside and downside-surrounding public debt projections as a result of uncertain economic conditions and policies. We propose a simulation algorithm for the path of public debt under realistic shock configurations, combining pure economic disturbances (to growth, interest rates, and exchange rates), the endogenous policy response to these, and the possible shocks arising from fiscal policy itself. The paper emphasizes the role of fiscal behavior, as well as the structure of disturbances facing the economy and due to fiscal policy, in shaping the risk profile of public debt. Fan charts for debt are derived from the "marriage" between the pattern of shocks on the one hand and the endogenous response of fiscal policy on the other. Applications to Argentina, Brazil, Mexico, South Africa, and Turkey are used to illustrate the approach and its limitations.